Nusselt number and fluid flow analysis of solar air heater having transverse circular rib roughness on absorber plate using LCT and computational technique. (December 2019) - Kumar, Amit; Layek, Apurba
Highlights: An experimental work using LCT approach with circular ribs placed on the absorber plate. The plate temperature is evaluated through thermo-liquid crystal sheets or LCT sheet. The effect of relevant geometric parameters is examined. The heat transfer enhancement in the form of Nusselt number or gain ratio is evaluated. Abstract: The present study compares the heat transfer distribution over the absorber surface of a solar air heater using liquid crystal thermography (LCT) technique along with a CFD technique. The heat transfer distribution over the absorber surface is measured using the LCT technique. Computational analysis (CFD) is performed using ANSYS FLUENT 16.2 code with a general algorithm for the air flow to visualize the characteristics and distribution of the flowing air through the duct. The LCT measurement shows a two-dimensional temperature distribution as a color dispersal over the absorber surface. Comparison of the results for two different parameters having relative roughness pitch (P/e) and relative roughness height (e/D) are represented in graphical form as the effect of Nusselt number and friction factor obtained using LCT with computational technique over Reynolds number (Re) ranges of 8, 551–11, 149. The image captured by the CCD Camera of the LCT techniques to give a temperature distribution over the surface and the results are scrutinized for optimum values for the considered range of parameter studied resulting for maximum values of heat transfer rate at roughness pitch ratio of 10 with a minimum penalty of frictional losses. This shows approximately similar values obtained from both the approaches.